Cloud Computing and ERP: A Framework of Promises and Challenges - Zhong, Fengze; Rohde, Max Erik (ACIS, 2014)
Enterprise Resource Planning (ERP) systems are an integral component of IT infrastructure in many organizations. A recent trend for ERP is the shift from on-premises infrastructure to the cloud environment through utilization of cloud computing technologies. The characteristics of cloud computing induces many promises to cloud-based ERP systems - making ‘Cloud ERP’ a favourable alternative to on-premises ERP systems. However, moving ERP systems into the cloud also presents many challenges. This paper aims to evaluate the promises and challenges of cloud-based ERP systems from a review of the literature and propose a framework to be of utility for IT executives and researchers to assess the key promises and challenges of cloud environments for ERP systems. The contribution of this paper is threefold. First, we identify a set of key promises and challenges to help IT decision makers and researcher to gain a better understanding of cloud computing and ERP. Second, our framework identifies four dimensions of cloud ERP to be assessed: Efficiency, Flexibility, Ubiquity, and Security. We propose that all these dimensions encompass promises and challenges to varying degrees. Third, we propose research opportunities for IS researchers in the domain of cloud-based ERP systems based on the identified four dimensions.